Peningkatan Hasil Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik Tema 7 Subtema 3 Di Kelas II Sekolah Dasar - Melisa, Melisa; Suardiman, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The aim of this research is to decribe the improvement of student achievement by using scientific approach in integrated thematic for theme 7 and subtheme 3 at the 2nd grade of SDN 34 Dadok Tunggul Hitam (elementary school) 2018/2019. This is a classroom action research by using quantitative and qualitative analysis. The research procedures are: planning, implementing, observing and reflecting. Research subjects are students in 2nd grade with 2 cycles. Research data was obtained from all cycles by using observation sheet and test. From the research results, in the first cycle 81,18% of the lesson plans are good (B) and in the second cycle 90,90% are very good (A). Teacher activities in the first cycle are 77,5% (B), in the second cycle increase to 95% (A). Students activities in the first cylce are 67,5% (C), in the second cycle increase to 90% (A). Students achievement in the first cycle are 66,4% (C) and in the second cycle increase to 87% (A). Based on this research we can conclude that the using of scientific learning could improve student achievement in integrated thematic for theme 7 subtheme 3 at the 2nd grade of SDN 34 Dadok Tunggul Hitam.